3D flow reactors: flow, hydrodynamics, and performance - Sharma, Mrityunjay; Reddy, Venkateswara S.; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2014)
A device comprised of a sequence of converging or diverging units aligned either in an axisymmetric or nonaxisymmetric manner can be used as a continuous flow reactor. Here we report the analysis of flow and hydrodynamics (pressure drop, residence time distribution, and mass transfer) for an axisymmetric geometry of a 3D flow reactor for single phase and two-phase flows. CFD simulations of the single phase flow have been used for identification of the precise geometrical configuration. The sequence of converging units as a flow reactor has been found to always be better than the sequence of diverging units. The residence time distribution analysis also favored the choice of converging flow as a better option. The performance of the device was verified by successfully carrying out a highly exothermic two-phase aromatic nitration of benzaldehyde (Delta H-r approximate to -172 kg/mol) with fuming nitric acid.